Plasma circulating cell-free mitochondrial DNA in depressive disorders. - Johan Fernström (Public Library of Science (PLoS), 2021)
Background Plasma circulating cell-free mitochondrial DNA (ccf-mtDNA) is an immunogenic molecule and a novel biomarker of psychiatric disorders. Some previous studies reported increased levels of ccf-mtDNA in unmedicated depression and recent suicide attempters, while other studies found unchanged or decreased ccf-mtDNA levels in depression. Inconsistent findings across studies may be explained by small sample sizes and between-study variations in somatic and psychiatric co-morbidity or medication status. Methods We measured plasma ccf-mtDNA in a cohort of 281 patients with depressive disorders and 49 healthy controls. Ninety-three percent of all patients were treated with one or several psychotropic medications. Thirty-six percent had a personality disorder, 13% bipolar disorder. All analyses involving ccf-mtDNA were a priori adjusted for age and sex. Results Mean levels in ccf-mtDNA were significantly different between patients with a current depressive episode (n = 236), remitted depressive episode (n = 45) and healthy controls (n = 49) (f = 8.3, p<0.001). Post-hoc tests revealed that both patients with current (p<0.001) and remitted (p = 0.002) depression had lower ccf-mtDNA compared to controls. Within the depressed group there was a positive correlation between ccf-mtDNA and "inflammatory depression symptoms" (r = 0.15, p = 0.02). We also found that treatment with mood stabilizers lamotrigine, valproic acid or lithium was associated with lower ccf-mtDNA (f = 8.1, p = 0.005). Discussion Decreased plasma ccf-mtDNA in difficult-to-treat depression may be partly explained by concurrent psychotropic medications and co-morbidity. Our findings suggest that ccf-mtDNA may be differentially regulated in different subtypes of depression, and this hypothesis should be pursued in future studies.